2019
DOI: 10.7759/cureus.4938
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Recent National Institutes of Health (NIH) Funding in General Surgery: Analysis Using the NIH RePORTER System

Abstract: Introduction: The National Institutes of Health (NIH) is the world’s largest funding source for research, and the R01 grant is seen as a stepping stone to future granting opportunities for the physician-scientist. Recently, both a gender and degree disparity in scholarly activity has been highlighted in the medical literature. Objective: To assess NIH R01 funding trends in general surgery over the last decade. Methods: A retrospective review of general surgery funding was extracted from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 11 publications
(11 reference statements)
2
23
0
Order By: Relevance
“…23 Men also tended to receive more prestigious grants or grants with more funding compared to women in several specialties. [23][24][25][26] Furthermore, an analysis of research grant applications for Harvard Medical School faculty found that female faculty had fewer grant submissions overall after controlling for academic rank. 27 The impact of female neurosurgeons with reduced research funding may contribute to the gender gap in authorship observed in journals such as Neurosurgery and the Journal of Neurosurgery.…”
Section: Discussionmentioning
confidence: 99%
“…23 Men also tended to receive more prestigious grants or grants with more funding compared to women in several specialties. [23][24][25][26] Furthermore, an analysis of research grant applications for Harvard Medical School faculty found that female faculty had fewer grant submissions overall after controlling for academic rank. 27 The impact of female neurosurgeons with reduced research funding may contribute to the gender gap in authorship observed in journals such as Neurosurgery and the Journal of Neurosurgery.…”
Section: Discussionmentioning
confidence: 99%
“…This included poor research infrastructure, representation on vital Federal committee's, low rate of Federal grants awarded and inclusion as editors in medical journals. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] A credit to our training and the make-up as a medical community; physicians tend to believe in others, favor trust and compliance. This same trait can lead to anergy at times when speaking up and taking action is more prudent.…”
Section: Editorialmentioning
confidence: 99%
“…Recent data have shown that very few osteopathic physicians serve as either the first or senior author in published original research manuscripts in emergency medicine, obstetrics and gynecology, pediatrics, and neurosurgery [1][2][3][4]. Additionally, no osteopathic physicians have been awarded a National Institutes of Health (NIH) R01 grant in emergency medicine, family medicine, general surgery, or obstetrics and gynecology in the previous decade [5][6][7][8]. Although we do not anticipate substantial differences in grants awarded to internal medicine investigators, no data currently exist on the scholarly activity between osteopathic and allopathic physicians within the specialty of internal medicine.…”
Section: Introductionmentioning
confidence: 99%